2018
DOI: 10.1177/1071100717745313
|View full text |Cite
|
Sign up to set email alerts
|

Syme Amputation: A Systematic Review

Abstract: Therapeutic Level III, systematic review containing retrospective cohort studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…17 In our study, 25% of Syme amputations later required a major amputation, which is in the range described in the previous literature (14.7%-38.5%). 7,17,19 Although most of our major amputations were due to DFO located in the forefoot, this occurred in 6% of forefoot DFO cases. Moon et al observed that 4.7% of forefoot ulcers in the setting of diabetes mellitus underwent later major amputation.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…17 In our study, 25% of Syme amputations later required a major amputation, which is in the range described in the previous literature (14.7%-38.5%). 7,17,19 Although most of our major amputations were due to DFO located in the forefoot, this occurred in 6% of forefoot DFO cases. Moon et al observed that 4.7% of forefoot ulcers in the setting of diabetes mellitus underwent later major amputation.…”
Section: Discussionmentioning
confidence: 96%
“… 17 In our study, 25% of Syme amputations later required a major amputation, which is in the range described in the previous literature (14.7%-38.5%). 7 , 17 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Most reports on these amputation levels have focused on patients with diabetes, peripheral vascular disease, infections, or tumors. While there are several small series and case reports in the literature on hind-and midfoot amputations for trauma, the heterogeneous injury types, surgical techniques, and reported outcome measures, and the small patient numbers without comparison groups make it difficult to interpret prior reports [23][24][25][26][27][28][29] . Our study was an attempt to compare outcomes of patients undergoing hind-and midfoot versus transtibial amputations after traumatic injury.…”
Section: Discussionmentioning
confidence: 99%
“…When plantar skin is used in the reconstruction of residual limbs, it performs better than skin from other donor sites 16,17 . The Syme amputation, named after the surgeon who pioneered it, uses heel pads (including the skin and fat pad) to reconstruct the lower residual limb; these individuals can walk directly on their stumps without incurring skin injury 18 . However, plantar skin is rarely available in sufficient quantities when reconstructing residual limbs.…”
Section: Premisesmentioning
confidence: 99%